Effects of Potassium and Manganese Promoters on Nitrogen-Doped Carbon Nanotube-Supported Iron Catalysts for CO2 Hydrogenation. (June 2017) - Kangvansura, Praewpilin; Chew, Ly May; Kongmark, Chanapa; Santawaja, Phatchada; Ruland, Holger; Xia, Wei; Schulz, Hans; Worayingyong, Attera; Muhler, Martin
Abstract: Nitrogen-doped carbon nanotubes (NCNTs) were used as a support for iron (Fe) nanoparticles applied in carbon dioxide (CO2 ) hydrogenation at 633 K and 25 bar (1 bar = 10 5 Pa). The Fe/NCNT catalyst promoted with both potassium (K) and manganese (Mn) showed high performance in CO2 hydrogenation, reaching 34.9% conversion with a gas hourly space velocity (GHSV) of 3.1 L·(g·h) −1 . Product selectivities were high for olefin products and low for short-chain alkanes for the K-promoted catalysts. When Fe/NCNT catalyst was promoted with both K and Mn, the catalytic activity was stable for 60 h of reaction time. The structural effect of the Mn promoter was demonstrated by X-ray diffraction (XRD), temperature-programmed reduction (TPR) with molecular hydrogen (H2 ), and in situ X-ray absorption near-edge structure (XANES) analysis. The Mn promoter stabilized wüstite (FeO) as an intermediate and lowered the TPR onset temperature. Catalytic ammonia (NH3 ) decomposition was used as an additional probe reaction for characterizing the promoter effects. The Fe/NCNT catalyst promoted with both K and Mn had the highest catalytic activity, and the Mn-promoted Fe/NCNT catalysts had the highest thermal stability under reducing conditions.